Learning leadership in outdoor education: Effects of feedback - Åge Vigane; Sindre M. Dyrstad (Cappelen Damm Akademisk NOASP, 2022)
There is paucity of knowledge regarding learning outcomes from outdoor leadership training courses. The aim of this pilot study was to examine progress in perceived leadership skills after a six-month outdoor education course, and to examine the effect of systematic feedback from fellow students. Seventeen students were randomized into intervention and control groups and participated in six outdoor excursions during which they took leader roles. The intervention consisted of systematic use of feedback from fellow students. To assess the progress in students' perceived outdoor leadership skills, the students answered a questionnaire covering four categories of leadership both before and after the course. Significant progress in perceived outdoor leadership was found for all students after the six-month course. Systematic feedback from fellow students did not seem to enhance students' perceived outdoor leadership skills. The reasons could be that the feedback was not given in the actual situations or that the student feedback was not valued. Feedback from teachers and from nature (self-experience) were found to be important for strengthening perceived leadership skills.